(untitled) (Philological Studies: Scientific Bulletin of Kryvyi Rih State Pedagogical University, 2016)
This article aims to present linguistic analysis of german veterinary vocabulary and is dedicated to study of historical formation of german veterinary termsystem. German veterinary vocabulary for many centuries formed and developed together with the science of animal husbandry. The words of Greek origin designated various organs, diseases and diagnoses. The words of Latin origin found in the anatomy and physiology of animals. The issue of term determination as it is, its relation to nomenclature and professional vocabulary have been researched in the article. It is required a systematic study of highly specialized terminology, since it has a special place among technical and common vocabulary, which are in constant interdependent relations. In the article it is considered the classification of veterinary terms, their structure and functioning. German veterinary vocabulary reflects a condition of the corresponding science and agriculture of Germany which is one of the most developed in the world. This terminology is in details developed and differs in rather high precision and compliance of the terms used in it. Results of research of this article have value for studying of lexicon of German and the German terminology of veterinary science of a particular. They will help to understand better possibilities of functioning of the certain words terms used in the context of veterinary terminology.